THE EFFECT OF USING CONTEXTUAL REDEFINITION STRATEGY ON STUDENTS’ READING NARRATIVE TEXT OF ELEVENTH GRADE AT SMA N 8 MEDAN - Yohana M Simanjuntak (JETAL: Journal of English Teaching & Applied Linguistic, 2019)
This study aimed to see the result of students’s achievement in reading narrative text with applyaing Contextual Redefinition Strategy. The population of the study was the elevent grade students of SMA N 8 Medan on 2019/2020 with the total number is 180 students. Two classes were taken as the sample they were IX IPA 4 and IX IPA 5. The experimental group was taught by using Contextual Redefinition while the control group (IX IPA 5) was taught by using conventional method. The instrument of collecting data was multiple choice test. The data were analyzed by using t-test. Based on the data, it was found that the students’ score improved from pre-test and post-test in experimental class. The result shoe that t-observed is higher that t-table value (2.9> 1.671) at the level significance 0,05 and the degree of freedom is 58. Therefore, it can be concluded that the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) ia accepted. Based on the research result, there is a significant effect of using Contextual redefinition strategy in eading Narrative test of Eleventh Grade Students’ at SMA N 8 Medan.